AQPETKEY ARXEPELAGI TUPROQ MAKROFAUNASINING BIOEKOLOGIK XUSUSIYATLARI. - Jumanov , M.A.; Isayev , R.T; Ilyasova , G.J.; Allashova , M.T. (Actual problems and prospects of the study of the fauna, 2024)
The relevance of the research: Environmental change is one of the main factors of the emergence of unique biogeocenosis and landscapes.Today, a bioecological disaster is occurring in the world due to the negative impact of astrogenic factors on people close to a person.One of them is the drying up of the Akpetkey archipelago.